2017
DOI: 10.1051/shsconf/20173600022
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Environmental, Social and Governance on the Corporate Performance of Malaysian Government-Linked Companies

Abstract: This study examines the impacts of ESG on the corporate performance government-linked companies (GLCs) in Malaysia. For the period 2006-2012, ESG disclosure data were extracted from the Sustainalytics ESG performance reports, while financial data were obtained from the Bloomberg database. Data development analysis (DEA) was used to estimate efficiency in the first stage; a regression analysis was performed to test the relationship between ESG and efficiency in the second stage. The empirical results of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Previous researchers that found a positive influence between ESG performance on economic were Ferreroferrero et al, (2016), Signes, Ona, Jimenez, & Vargas (2013), Michelon, Boesso, & Kumar (2013), Roman, Hayibor, &Agle (1999), Simpson & Kohers (2002), Orlitzky, Schmidt, Rynes, &Rynes (2000), and Al-tuwaijri& Ii (2003). Meanwhile, studies that found negative results were Crisostomo, Freire, & Vasconcellos (2011).Other studies from Tarmuji, Maelah, & Tarmuji(2016), Dahlberg & Wiklund (2018), Waworuntu, Wantah, & Rusmanto (2014), Long, Bakhtiar, Chuann, Abdullah, & Mohammad (2017), and Velte (2018) found mixed results with the different object and variables.…”
Section: Introductionmentioning
confidence: 94%
“…Previous researchers that found a positive influence between ESG performance on economic were Ferreroferrero et al, (2016), Signes, Ona, Jimenez, & Vargas (2013), Michelon, Boesso, & Kumar (2013), Roman, Hayibor, &Agle (1999), Simpson & Kohers (2002), Orlitzky, Schmidt, Rynes, &Rynes (2000), and Al-tuwaijri& Ii (2003). Meanwhile, studies that found negative results were Crisostomo, Freire, & Vasconcellos (2011).Other studies from Tarmuji, Maelah, & Tarmuji(2016), Dahlberg & Wiklund (2018), Waworuntu, Wantah, & Rusmanto (2014), Long, Bakhtiar, Chuann, Abdullah, & Mohammad (2017), and Velte (2018) found mixed results with the different object and variables.…”
Section: Introductionmentioning
confidence: 94%
“…Annual reports for the year 2019 of the sample companies were chosen as secondary data information for data collection purposes. The extent of disclosures made through annual reports can be considered for this study as there were many previous studies which used annual reports as a channel for information (Ahmad, Hassan, & Mohammad, 2003;Kweh et al, 2017;Haniffa & Cooke, 2005;Mohd Ghazali, 2007;Atan et al, 2016).…”
Section: Methodology Population Sample and Data Collectionmentioning
confidence: 99%
“…These three main dimensions help measure not only financial performance but also future performance of corporations. Past studies have shown that different corporations have different strategies to outfit for ESG disclosures, giving an impact towards financial performance (Friede, Busch, & Bassen, 2015;Ruhaya, Razali, Said, & Zainon, 2016;Kweh, Alrazi, Chan, Abdullah, & Lee, 2017;Tze et al, 2016;Zhao, 2018). The results are inconclusive as they are mixed between positive and contradictory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the past, especially in the context of Malaysia as one of the high performing emerging economies with GDP per capita growth of more than 3.5% annually https: //doi.org/10.15405/epsbs.2020.12.05.29 Corresponding Author: Bakhtiar Alrazi Selection and peer-review under Sulaiman et al (2014), Said et al (2013), Alrazi et al (2009), Buniamin et al (2008), Sumiani et al (2007), and Ahmad et al (2003), to name but a few. Recently, there was a shift from researching on environmental reporting to broader sustainability reporting (Amran et al, 2014;Amran & Haniffa, 2011;Sawani et al, 2010) or environmental, social and governance (ESG) reporting (Kweh et al, 2017). Furthermore, there has also become a trend to examine a rather more specific environmental issues including climate change (e.g., Alrazi, 2014;Amran et al, 2012;Kalu et al, 2016;Ooi & Amran, 2018;Omar & Amran, 2017), water and biodiversity (Mat Husin et al, 2018a, 2018b.…”
Section: Problem Statementmentioning
confidence: 99%